The resurrection of Charles Manson [videorecording (DVD)] - Grillo, Frank, 1963-; King, Jaime, 1979-; Dumont, Sarah, 1990-; Peltz, Will, 1986-; Moss, Brev; Plasse, Josh (Decal, 2023)
A couple goes away for a romantic weekend but quickly becomes the target of a Cult. This new Manson Family believes they can resurrect the object of their obsession, Charles Manson himself, through a shocking ritual of human sacrifice.